Factors that motivate the investor in choosing Malaysia as an operation place for halal manufacturing / Nurliana Hisham - Hisham, Nurliana (2017)
The growing of Halal Industry is increasing day by day. Not only in Asia region but also worldwide. The increasing demand for Halal product has made the number of Halal manufacture increase as well despite the difference of production they have made.